2012
DOI: 10.1371/journal.pone.0052861
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Evaluation of Bone Loss at Implants with Biocide Coated Titanium Abutments: A Study in the Dog

Abstract: The objective of the present study is to evaluate bone loss at implant abutments coated with a soda-lime glass containing silver nanoparticles subjected to experimental peri-implantitis. Five beagle dogs were used in the experiments, 3 implants were installed in each quadrant of the mandibles. Glass/n-Ag coted abutments were connected to implant platform. Cotton floss ligatures were placed in a submarginal position around the abutment necks and the animals were subject to a diet which allowed plaque accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…For a comparative purpose, a soda-lime glass containing silver nanoparticles is also evaluated. The efficacy of this kind of glass to prevent peri-implant diseases was pointed out in previous works [ 21 , 22 ]…”
Section: Introductionmentioning
confidence: 97%
“…For a comparative purpose, a soda-lime glass containing silver nanoparticles is also evaluated. The efficacy of this kind of glass to prevent peri-implant diseases was pointed out in previous works [ 21 , 22 ]…”
Section: Introductionmentioning
confidence: 97%
“…In another study nanosilver coating of implants is shown to reduce the risk of peri-implantitis18. In the antimicrobial activity test no growth inhibition was seen around the control and uncoated material, and a minimal growth inhibition was observed around the silver ion coated bands.…”
Section: Discussionmentioning
confidence: 97%
“…119 Implants with titanium abutments coated by a soda lime glass containing silver nanoparticles are capable of constraining the experimentally induced peri-implantitis bone loss. This particular coating decreases the total bone recession caused by induced periimplantitis, [120][121][122] but causes an initial time-limited gingival inflammation. 120,122 Silver nanoparticles deposited by anodic spark deposition in combination with a solution containing silicon, calcium, phosphorus, and sodium for a biomimetic coating on titanium substrates was able to reduce bacterial adhesion and provide osteointegrative properties.…”
Section: Nonantibiotic Antimicrobial Coatingsmentioning
confidence: 99%
“…This particular coating decreases the total bone recession caused by induced periimplantitis, [120][121][122] but causes an initial time-limited gingival inflammation. 120,122 Silver nanoparticles deposited by anodic spark deposition in combination with a solution containing silicon, calcium, phosphorus, and sodium for a biomimetic coating on titanium substrates was able to reduce bacterial adhesion and provide osteointegrative properties. 123 Besides silver, other inorganic agents, such as copper, 113,124 fluorine, 125,126 and zinc 15,124 have been introduced as potential antimicrobial agents in dental implant coatings.…”
Section: Nonantibiotic Antimicrobial Coatingsmentioning
confidence: 99%